White matter tractography of the neural network for speech-motor control in children who stutter. (6th March 2018) - Misaghi, Ehsan; Zhang, Zhaoran; Gracco, Vincent L.; De Nil, Luc F.; Beal, Deryk S.
Highlights: Seven white matter tracts were assessed using diffusion tensor tractography. CWS had higher FA and AD in the right FAT relative to the left FAT. Controls had higher AD in the left FAT as compared to the right FAT. The right FAT in CWS had higher FA and AD than controls. Abstract: Stuttering is a neurodevelopmental speech disorder with a phenotype characterized by speech sound repetitions, prolongations and silent blocks during speech production. Developmental stuttering affects 1% of the population and 5% of children. Neuroanatomical abnormalities in the major white matter tracts, including the arcuate fasciculus, corpus callosum, corticospinal, and frontal aslant tracts (FAT), are associated with the disorder in adults who stutter but are less well studied in children who stutter (CWS). We used deterministic tractography to assess the structural connectivity of the neural network for speech production in CWS and controls. CWS had higher fractional anisotropy and axial diffusivity in the right FAT than controls. Our findings support the involvement of the corticostriatal network early in persistent developmental stuttering.